Reconstruction Of Diversion Policy In Handling Children Of Criminal Offenders A Comparative Study Of Law - Herianto, Muhammad Firza; Alhakim, Abdurrakhman; Hutauruk, Rufinus Hotmaulana (UNIVERSITAS PAKUAN, 2025)
AbstracktThis study analyzes the limitations of diversion in the Indonesian Juvenile Criminal Justice System, specifically the requirements for implementing diversion, namely a sentence of less than 7 years and not repeat offenses. This study applies normative juridical research methods through a statutory and comparative legal approach. The study compares the application of restorative justice approaches in the Philippines through the Republic Act No. 10630 of 2013 and in New Zealand through the Oranga Tamariki Act 1989. The findings reveal that Indonesia's diversion policy remains limited by sentencing threats and repeat offenses, forcing children to undergo formal judicial proceedings. This condition contradicts the principle of child protection, which prioritizes rehabilitation and social reintegration. As a recommendation, this study proposes reconstructing Indonesia's diversion policy by referring to the experiences of the Philippines and New Zealand to establish a more inclusive, humane, and restorative-based juvenile justice system. Keywords: Diversion, Restorative Justice, Reconstruction.